Transfer of high grain zinc from Triticum monococcum and Triticum boeoticum to hexaploid wheat varieties and advanced lines using T. durum as a bridging species - Singh, Charan; Srivastava, Puja; Sharma, Achla; Chhuneja, Parveen; Sohu, Virinder Singh; Mavi, Gurvinder Singh; Kaur, Harinderjeet; Bains, Navtej Singh (Journal of Cereal Research, 2016)
A set of 10 potential donors resulted from introgression of high grain zinc accessions of A genome diploid species in durum wheat background (Triticum monococcum acc. W49-27-1/2*Aconchi89 and T. boeoticum acc. 4992/2*PDW274) were crossed with 03 hexaploid wheat cultivars (WH 1105, DPW 621-50, HD 2967) and 02 advanced lines (PBW 698, PBW 703). Â A total of 1077 BC2F2 derivatives from 33 of the all possible 50 crosses, were subjected to estimation of grain zinc and iron concentration, grain protein content, 1000-grain weight, plant height, days to heading, days to maturity, grain yield and significant genotypic variation was observed for all these traits. Twenty five lines from six crosses showed very high grain zinc concentration ranging from 84.1 to 93.7 ppm as compared to 53.26 to 64.50 ppm observed in the set of recipient parents. A further subset of 07 lines that displayed high grain iron concentration, protein content and 1000-grain weight, six of these lines were also found highly resistant to stripe rust and possessed desirable agronomic features and thus could be useful for further selection and direct use in varietal development. T. monococcum acc. W49-27-1/2*Aconchi89 proved to be the better donor, while 02 advanced lines namely PBW 698 and PBW 703 possessing Â rust resistance genes Lr24, Lr28, Yr10 and Yr15 in PBW 343 background proved to be the most effective recipients.